Case report: anti-Coa in a Co-(a+)-typed patient with chronic renal insufficiency - Leo, Albrecht; Cartron, J. P.; Strittmatter, M.; Rowe, G.; Roelcke, Dieter (Beiträge zur Infusionstherapie und Transfusionsmedizin, 1997)
The recently identified molecular structure of the Colton blood group system is characterized by an amino acid substitution at position 45 (Colton a: alanine, Colton b: valine) of the archetypical water channel protein Aquaporin-1 (AQP1), which regulates water homeostasis in the erythrocyte membrane and in the proximal tubule of the nephron. We identified a patient with the unique constellation of an antibody with the specificity anti-Coa and the Co (a+) phenotype. The serological antigen typing was confirmed by molecular typing with PCR-RFLP. The antibody has to be interpreted as an antibody against a partial Colton a antigen or as an autoantibody despite a negative direct antiglobulin test (DAT). The patient is suffering from chronic renal insufficiency of unknown origin, rising speculation about a pathophysiological relationship between the serological constellation and the clinical disease under the aspect of localization of the Colton antigens on AQP1.